Sick Building Syndrome Incidence by Age and Work Period: A Regression Analysis - Jusuf, Herlina; Tarigan, Sylva Flora Ninta; Yunus, Hairun Nisa; Abudi, Ramly; Arsad, Nikmatini; Adityaningrum, Amanda (Universitas Muhammadiyah Palu, 2024)
Many nonspecific symptoms of illness can occur as a result of exposure to specific harmful agents at certain workplaces, which is commonly referred to as Sick Building Syndrome (SBS). Several factors may contribute to the incidence of SBS, such as an individual’s age and work period. This research aims to determine the impact of age and work period on the incidence of SBS among employees at Telkom Gorontalo’s IT department. Cross-sectional observations were carried out in this research. Researchers conducted saturation sampling (total sampling) using all of Telkom Gorontalo’s IT employees as a sample population. Following this, 35 IT employees were used as samples. According to the analysis results, among the 35 IT employees working for Telkom Gorontalo, 27 had SBS incidents. In addition, out of 35 IT employees, 28 were under 40, 27 had standard working hours (work for 8 hours), and 14 had worked at Telkom Gorontalo for less than three years. A logistic regression analysis revealed that age significantly contributed to SBS incidence among Telkom Gorontalo’s IT employees (p-value = 0,001). Furthermore, the R-Square value was calculated using logistic regression, which is 46,45%.